Bipolar Fuzzy Commutative Ideals in BCK-algebras (European Journal of Pure and Applied Mathematics, 2024)
This paper presents the concept of the notions of bipolar fuzzy commutative ideals of a BCK-algebra. We also study various properties regarding this concept. We prove various characterisations for bipolar fuzzy commutative ideals. Moreover, a relationship between bipolar fuzzy commutative ideals and bipolar fuzzy positive implicative ideals is presented. In addition, we present the notation of bipolar fuzzy characteristic commutative ideal. Then a relationship between a bipolar fuzzy characteristic commutative ideal and its level-cut commutative ideals is provided.
Keywords: Bipolar fuzzy ideal, positive implicative ideal, characteristic ideal.